Early detection and optimization of early childhood growth and development - Karima, Karima; Lubis, Eka Jelita; Nabila, Mauliza; Khairani, Rida; Nasution, Homsani (Lembaga Riset Mutiara Akbar, 2026)
Early childhood development is the main foundation for the quality of human resources in the future, therefore it requires serious attention through early detection and efforts to optimize sustainable growth and development. This article aims to examine the concept of early detection of early childhood growth and development and analyze its role in optimizing child development based on the findings of the latest research. This research uses a qualitative approach with a systematic literature review method. Data sources were obtained from academic books, articles from national journals accredited by SINTA 1–3, and reputable international journals published between 2020–2024. Data analysis was conducted through content analysis and thematic analysis to identify key concepts, patterns of findings, and the relationship between early detection and optimization of early childhood growth and development. The results of the study indicate that early detection is a systematic process that encompasses aspects of physical growth, cognitive development, language, socio-emotional, and child behavior. Early detection followed by appropriate stimulation and intervention has been shown to have positive implications for optimizing child growth and development holistically. This study confirms that early detection functions not only as a screening tool, but also as a strategic foundation in planning integrated, collaborative, and sustainable early childhood development stimulation.